Pengaruh Internet Banking Terhadap Kepuasan Nasabah Pada PT. Bank Bri Syariah Kebayoran Baru - Budi Syamtoro (Peneliti.net, 2020)
This study aims to determine the effect of Internet Banking on Customer Satisfaction at PT. Bank BRI Syariah Kebayoran Baru. The method used is explanatory research with a sample of 89 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study, the Internet Banking variable obtained an average score of 3.406 with good criteria. The Customer Satisfaction variable obtained an average score of 3,793 with good criteria. Internet Banking has a positive and significant effect on Customer Satisfaction with a regression equation value of Y = 10.620 + 0.802X, and a correlation coefficient value of 0.749 or has a strong level of relationship with a determination value of 56.1%. Hypothesis testing obtained a significance of 0.000 <0.05.